Prevalence and outcomes associated with hypocalcaemia and hypercalcaemia among pre-dialysis chronic kidney disease patients with mineral and bone disorder - Mei Hui Amanda Yong; Jun Jie Benjamin Seng; Ying Lin Cheryl Tan; Jiunn Wong; Priscilla How (Singapore Medical Journal)
Introduction: Chronic kidney disease-mineral and bone disease (CKD-MBD) is a complication of chronic kidney disease (CKD) involving derangements in serum calcium and phosphate. This study aims to evaluate hypo- and hypercalcaemia and their associated outcomes among pre-dialysis CKD patients. Methods: A retrospective cohort study was performed and included all adult CKD stage 4–stage 5 patients who were on treatment for CKD-MBD between 2016 and 2017. Each patient was followed up for 3 years. Hypo- and hypercalcaemia were defined as serum corrected calcium (Ca2+) <2.10 and >2.46 mmol/L, respectively. Outcomes evaluated included all-cause mortality and cardiovascular events. Multivariate Cox regression analysis was done to evaluate the association of hypocalcaemia and/or hypercalcaemia with the clinical outcomes. Severity of hypocalcaemia episode was classified as ‘mild’ (Ca2+: between 1.90 and 2.10 mmol/L) and ‘severe’ (Ca2+: <1.90 mmol/L). Severity of hypercalcaemia was classified as ‘mild’ (Ca2+: between 2.47 and 3.00 mmol/L), moderate (Ca2+: between 3.01 and 3.50 mmol/L) and severe (Ca2+: >3.50 mmol/L). Results: Of the 400 patients, 169 (42.2%) and 94 (23.5%) patients experienced hypocalcaemia and hypercalcaemia, respectively. Severe hypocalcaemia was more prevalent in CKD stage 5 compared to CKD stage 4 (96 [40.5%] vs. 36 [25.9%], P = 0.004). Results from multivariate analyses after adjustment showed that hypocalcaemia and/or hypercalcaemia were not associated with all-cause mortality (P > 0.05) or the occurrence of cardiovascular events (P > 0.05). Conclusion: Hypocalcaemia and hypercalcaemia episodes were prevalent among pre-dialysis CKD patients. Studies with longer follow-up durations are required to assess the effects of calcium derangements on clinical outcomes.